2005
DOI: 10.1074/jbc.m503262200
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Sites in the MyD88 Toll/Interleukin (IL) 1 Receptor Domain Responsible for Coupling to the IL1β Signaling Pathway

Abstract: Myeloid differentiation factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 27 publications
3
82
3
1
Order By: Relevance
“…When a TIR mutant harboring a substitution of a functionally important residue is expressed, such suppression is alleviated, which leads to higher LPS-induced luciferase activity than observed with a TIR domain harboring the wild-type sequence. It should be noted that the dominant negative effect of ectopically expressed TIR domain has been used for functional analysis of some key residues of MyD88-TIR in IL-1 signaling (11).…”
Section: Cell-based Functional Assays Of the Myd88 Tir Domain In Tlr4mentioning
confidence: 99%
See 1 more Smart Citation
“…When a TIR mutant harboring a substitution of a functionally important residue is expressed, such suppression is alleviated, which leads to higher LPS-induced luciferase activity than observed with a TIR domain harboring the wild-type sequence. It should be noted that the dominant negative effect of ectopically expressed TIR domain has been used for functional analysis of some key residues of MyD88-TIR in IL-1 signaling (11).…”
Section: Cell-based Functional Assays Of the Myd88 Tir Domain In Tlr4mentioning
confidence: 99%
“…However, the functional relevance of these homomeric interactions remains obscure because the formation of a homomeric dimer in these TIR domains has not been observed in solution (9,10). Based on crystal structures and mutational data, several structural models have been proposed for heteromeric TIR-TIR interactions, which commonly suggest the importance of the so-called BB loop in these interactions (11,12).…”
mentioning
confidence: 99%
“…Despite extensive structural studies, it is not known why homotypic interactions are essential for downstream signaling (20)(21)(22)(23)(24)(25)(26)(27). To address this issue, it is necessary to discriminate residues required for homotypic and those required for heterotypic interactions.…”
mentioning
confidence: 99%
“…For this reason, they have been the subject of numerous structural and functional studies aimed at identifying the residues participating to homo and hetero interactions (21)(22)(23)(24)(25)(26). In the case of MyD88, it was demonstrated that the BB loop of the TIR domain plays a role in homodimerization (22,27,28).…”
mentioning
confidence: 99%